2009
DOI: 10.1007/s00125-009-1267-1
|View full text |Cite
|
Sign up to set email alerts
|

The inflammatory receptor CD40 is expressed on human adipocytes: contribution to crosstalk between lymphocytes and adipocytes

Abstract: Aims/hypothesis Obesity is associated with adipose tissue inflammation. The CD40 molecule, TNF receptor superfamily member 5 (CD40)/CD40 ligand (CD40L) pathway plays a role in the onset and maintenance of the inflammatory reaction, but has not been studied in human adipose tissue. Our aim was to examine CD40 expression by human adipocytes and its participation in adipose tissue inflammation. Methods CD40 expression was investigated in human whole adipose tissue and during adipocyte differentiation by real-time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
102
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(112 citation statements)
references
References 43 publications
(50 reference statements)
8
102
0
2
Order By: Relevance
“…CD40-CD40L interactions induce T-cell and APC activation, cytokine production, and B-cell isotype class switching as well as endothelial cell activation and monocyte migration (32,38,39,56). The expression of CD40 on AT cells, including adipocytes, stromal AT cells, and immune cells, positively correlates with BMI (57). Although the expression of membrane-bound CD40L is restricted to immune cells and stromal cells within the AT, soluble CD40L (sCD40L), mainly derived from activated platelets and T cells, may also activate CD40 + adipocytes (38,39,57).…”
Section: Cd40-cd40lmentioning
confidence: 99%
See 2 more Smart Citations
“…CD40-CD40L interactions induce T-cell and APC activation, cytokine production, and B-cell isotype class switching as well as endothelial cell activation and monocyte migration (32,38,39,56). The expression of CD40 on AT cells, including adipocytes, stromal AT cells, and immune cells, positively correlates with BMI (57). Although the expression of membrane-bound CD40L is restricted to immune cells and stromal cells within the AT, soluble CD40L (sCD40L), mainly derived from activated platelets and T cells, may also activate CD40 + adipocytes (38,39,57).…”
Section: Cd40-cd40lmentioning
confidence: 99%
“…The expression of CD40 on AT cells, including adipocytes, stromal AT cells, and immune cells, positively correlates with BMI (57). Although the expression of membrane-bound CD40L is restricted to immune cells and stromal cells within the AT, soluble CD40L (sCD40L), mainly derived from activated platelets and T cells, may also activate CD40 + adipocytes (38,39,57). Clinical studies have demonstrated that sCD40L plasma levels are increased in obese patients and positively correlate with BMI, waist circumference, fasting glucose, and leukocyte counts and that sCD40L levels decrease after bariatric surgery (58).…”
Section: Cd40-cd40lmentioning
confidence: 99%
See 1 more Smart Citation
“…After 48 h (d0), the medium was removed and replaced by Dulbecco's modified Eagle's medium containing 2 mM insulin only. Human subcutaneous preadipocytes and mouse embryonic fibroblasts were obtained as already described (19,20). Human visceral preadipocytes were from Lonza (Levallois-Perret, France).…”
Section: Cell Culture Differentiation and Transfectionmentioning
confidence: 99%
“…This allows for substantial cross-talk between these different cell types though cell-cell contact, surface molecular receptors and secreted factors. This communication between the cells is essential for the normal functioning of adipose tissue and this complex-reciprocal signaling has been demonstrated by in vitro co-culture experiments [5][6][7]. We have previously demonstrated that unique secretion profiles can be obtained from different adipose-derived cell populations [8].…”
Section: Introductionmentioning
confidence: 91%